Agronomic traits of rice hybrids (Oryza sativa L.) derived from new plant type and male sterile parents - Desi Anugra Safitri; Willy Bayuardi Suwarno; Ayub Darmanto; Hajrial Aswidinnoor (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2023)
Hybrid rice is derived from a cross between the cytoplasmic male sterile (CMS) as the female parent and the restorer line as the male parent. This study aimed to evaluate the ability of several new plant type (NPT) rice lines as restorers of the CMS female parent and to elucidate the performance of the hybrid combinations. The research was carried out from December 2019 to November 2020 at Babakan Sawah Baru Experimental Station, Department of Agronomy and Horticulture, IPB University, Bogor, Indonesia. The hybrids were evaluated in the field together with the CMS female parent, male parents, and two check varieties, namely Ciherang and hybrid P05 Prima Seed. The experimental design used was a randomized complete block design (RCBD) with two replications. The results showed that two male parental lines, IPB189-F-10-3-2 (T6) and IPB189-14-1-1 (T9), had a hybrid seed yield per hill of 66.04 g and 75.27 g, respectively. These two parents have the restorer gene (R) which is substantiated by the good characteristics of the number of filled grains and total grain per panicle of the two hybrids. The potential hybrids CMS x IPB189-F-10-3-2 and CMS x IPB189-14-1-1 had a positive heterosis for panicle length and 1,000 grain weight, and could be evaluated in future research. Keywords: CMS; heterosis; heterobeltiosis; rice hybrid